Il monastero di San Saturnino a Cagliari: storia di un edificio scomparso - Martorelli, Rossana (O T I V M, 2023)
The paper traces the monumental and archaeological history of the monastic complex of San Saturnino in Cagliari, to redesign this important context for the life of the city and for the diffusion of monasticism in the island. The collation of the evidence and the re-reading of the same in chronological order allow us to put forward some hypotheses regarding the frequentation but also perhaps the abandonment in some critical moments of the history of Cagliari in the early Middle Ages.